Potential Targets for CRISPR/Cas Knockdowns to Enhance Genetic Resistance Against Some Diseases in Wheat (Triticum aestivum L.) - Taj, Mehwish; Sajjad, Muhammad; Li, Mingju; Yasmeen, Arooj; Mubarik, Muhammad Salman; Kaniganti, Sirisha; He, Chi (Frontiers in Genetics, 2022)
Wheat is one of the most important food crops worldwide. Even though wheat yields have increased considerably in recent years, future wheat production is predicted to face enormous challenges due to global climate change and new versions of diseases. CRISPR/Cas technology is a clean gene technology and can be efficiently used to target genes prone to biotic stress in wheat genome. Herein, the published research papers reporting the genetic factors corresponding to stripe rust, leaf rust, stem rust, powdery mildew, fusarium head blight and some insect pests were critically reviewed to identify negative genetic factors (Susceptible genes) in bread wheat. Out of all reported genetic factors related to these disease, 33 genetic factors (S genes) were found as negative regulators implying that their down-regulation, deletion or silencing improved disease tolerance/resistance. The results of the published studies provided the concept of proof that these 33 genetic factors are potential targets for CRISPR/Cas knockdowns to improve genetic tolerance/resistance against these diseases in wheat. The sequences of the 33 genes were retrieved and re-mapped on the latest wheat reference genome IWGSC RefSeq v2.1. Phylogenetic analysis revealed that pathogens causing the same type of disease had some common conserved motifs and were closely related. Considering the significance of these disease on wheat yield, the S genes identified in this study are suggested to be disrupted using CRISPR/Cas system in wheat. The knockdown mutants of these S genes will add to genetic resources for improving biotic stress resistance in wheat crop.